Fostering Environmental Awareness Through Sustainable Development Goal-Oriented Ethno-STEM Approach in Elementary Education - Pada, Amir; Chanunan, Skonchai; Rahmat, Irwandi (Universitas Negeri Semarang, 2025)
This study examines the effectiveness of a Sustainable Development Goals (SDGs)-oriented Ethno-STEM approach in promoting environmental awareness among elementary school students through natural and social science learning. Utilizing a quasi-experimental one-group pretest-posttest design, the research involved 60 students from an elementary school in Makassar, Indonesia. Environmental awareness was assessed before and after the implementation of Ethno-STEM-integrated lessons that incorporated culturally relevant and participatory activities such as eco-brick making, waste management simulations, and the